EVALUATION OF LEAD LEVEL IN VARIOUS TISSUES OF PIGEONS (Columbia livia) IN YOGYAKARTA - Edi Boedi Santosa; Bambang Hariono; Mudasir Mudasir (Jurnal Sain Veteriner, 2000)
Lead is one of major air pollutants. Lead is a dangerous poison for human and animals. Pigeon meat is one of popular food consumed by many people in Yogyakana. The aim of this research was to evaluate whether the lead concentration in the pigeon in Yogyakarta is considered safe for human consumption or not Forty birds 3-4 months old were collected from 4 locations in Yogyakarta, Group I (10 birds) were collected from people who sole fried birds around UripBumodibflTjo, C. Simanjuntak, Kaliurang, Gcjayan, Johanes streets, and North Ringroad. Group II (10 birds) were collected from the bird markets (Ngasem, Terban, Lempuyangan), group III (10 birds) were collected from the bird owners who raised the birds extensivelly (not in cages). Group IV (10 birds) were obtained from the bird owners who raised tho birds imeosivdly (in cages). All experimental animals were euthanized by chloroform then necropsied. Kidney, liver and breast muscle were collected for lead examination using atomic absorption spectrophotorneter {AAS). The results of the experiment showed that lead concentrations in the kidneys, liver and breast muscle of pigeons obtained from several locations in Yogyakarta were higher than the recommended standard value from WHO (0,1 ppm).